(untitled) (International Journal of Built Environment and Sustainability, 2025)
Value engineering of construction projects has been instantiated through value workshops with realizable objectives to the benefit of the project owners and end-users. However, myriads of studies have indicated varying perspectives regarding the levels of value engineering (VE) awareness among the building, construction, engineering, (BCE) and allied professionals in Nigeria. This is coupled with the observed fallout of their experiential inadequacy in VE practice. It is against this backdrop that this study evaluated using the ten value workshop objectives (VWOs), the degree of association between VE awareness and VE proficiency among the BCE and allied professionals in Kogi State, Nigeria. Sequel to a pilot study, a combination of purposive sampling, and "stratified" snowballing of 365 questionnaires among Architects, Builders, Engineers, Estate Surveyors and Valuers, Project Managers, Quantity Surveyors, and Town Planners in the study area were instantiated. Consequently, 94 usable questionnaires were successfully retrieved and validated. Cross-tabulations were used to present the results of data analyses. It was found at p > 0.05, that the strong levels of VE awareness among the sample of these professionals did not necessarily imply that they might exhibit high levels of proficiency in VE practice. Although the results of the Fisher’s exact- and Barnard tests indicated a convergence between Project managers’ expected- and existing VE skills, the Chi-square test on the seven groups of professionals, however indicated a divergence; so that their experiential inadequacies in VE practice might be attributed to this divergence. Besides availing insight into the timely review of pedagogic- and pre-qualification processes for BCE and allied professionals who intend venturing into value methodology practice in Nigeria, this study is among the novel attempts at using VWOs as instruments for assessing the degree of association between VE awareness and VE proficiency among these professionals.